Feeding Five Billion Asians : A Socioeconomic Perspective - Cuesta, Jose (World Bank, Washington, DC, 2013)
This paper reviews the prospects for long-term food security in Asia, where a significant number of malnourished individuals still live after decades of mixed progress. Evidence shows that poverty reduction on its own will not do the job of eradicating hunger, nor will only increased food production. The region's contribution to high and volatile international food prices is well known, but Asia's potential contributions toward future decreased price uncertainty are much less cited. The changing composition of future food demand in the region will depend on the extent to which poverty reduction effectively leads to middle class expansion, which remains unclear.